2011
DOI: 10.1111/j.1465-3362.2011.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cannabis abuse/dependence symptoms and life satisfaction in young adulthood

Abstract: These findings suggest that associations between life substance abuse/dependence and life satisfaction can be explained by time-dynamic factors, such as employment, life events and comorbid mental illness that are associated with reduced life satisfaction. When due allowance is made for confounding, alcohol and cannabis abuse/dependence are not associated with reduced life satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
5
22
0
Order By: Relevance
“…Moreover, while it is almost impossible to estimate the unique effects of cannabis on cancer given high co-occurring rates of cannabis and tobacco use, cannabis has four times the amount of tar as cigarettes and causes similar damage to the mucous membranes in the trachea and bronchi that is associated with increased risk of lung and bronchial cancers (Dennis et al, 2002). Finally, cannabis use has also been associated with motor vehicle accidents and driving impairments, non-traffic injuries, emergency department admissions, drug-related deaths, mortality following treatment of cannabis use disorders, legal problems other than for cannabis possession or trafficking, reduced work commitment, reduced life satisfaction among individuals with cannabis use disorder symptoms, negative psychosocial parameters among patients with fibromyalgia, impulsivity among recreational/non-dependent cannabis users, and alterations of theory of mind network activation (Arendt, Munk-Jorgensen, Sher, & Jensen, 2013;Barrio et al, 2012;Bosker et al, 2012;Dennis et al, 2002;Downey et al, 2013;Hyggen, 2012;Moreno et al, 2012;Roser et al, 2012;Ste-Marie, Fitzcharles, Gamsa, Ware, & Shir, 2012;Swain, Gibb, Horwood, & Fergusson, 2012).…”
Section: Benefits and Harms Of Cannabis Usementioning
confidence: 99%
“…Moreover, while it is almost impossible to estimate the unique effects of cannabis on cancer given high co-occurring rates of cannabis and tobacco use, cannabis has four times the amount of tar as cigarettes and causes similar damage to the mucous membranes in the trachea and bronchi that is associated with increased risk of lung and bronchial cancers (Dennis et al, 2002). Finally, cannabis use has also been associated with motor vehicle accidents and driving impairments, non-traffic injuries, emergency department admissions, drug-related deaths, mortality following treatment of cannabis use disorders, legal problems other than for cannabis possession or trafficking, reduced work commitment, reduced life satisfaction among individuals with cannabis use disorder symptoms, negative psychosocial parameters among patients with fibromyalgia, impulsivity among recreational/non-dependent cannabis users, and alterations of theory of mind network activation (Arendt, Munk-Jorgensen, Sher, & Jensen, 2013;Barrio et al, 2012;Bosker et al, 2012;Dennis et al, 2002;Downey et al, 2013;Hyggen, 2012;Moreno et al, 2012;Roser et al, 2012;Ste-Marie, Fitzcharles, Gamsa, Ware, & Shir, 2012;Swain, Gibb, Horwood, & Fergusson, 2012).…”
Section: Benefits and Harms Of Cannabis Usementioning
confidence: 99%
“…Extant longitudinal studies generally have not found significant relationships between cannabis use and quality of life (e.g., Swain et al, 2012; Bogart et al, 2007). In contrast, one longitudinal study of offspring of pregnant women in Australia revealed that those who used cannabis more frequently had a lower quality of life at a later time (Fischer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The few available cross-sectional studies have reported that higher frequencies of cannabis use were assoicatd with poorer quality of life (Green et al, 2004; Swain et al, 2012). One exception is a cross-sectional study by Allen & Holder (2014) which found no relationship between frequency of cannabis use and well-being among 570 undergraduate students (Allen & Holder, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since impulsivity and lack of self-control are commonly present among compulsive buyers (Black et al, 2012; Claes et al, 2011), we also controlled for impulsivity in our study. Some studies have shown that substance use/disorder is associated with low quality of life (Swain et al, 2012) and CB (Lejoyeux et al, 2006; Mitchell et al, 2002; Roberts and Tanner, 2000). For example, Roberts and Tanner (2000) found that self-report measures of illegal drug use were significantly associated with CB among teenagers (12–19 years).…”
Section: Introductionmentioning
confidence: 99%